The Seed Morphology and Germination Behavior of Sesbania grandiflora L. Under Nursery Conditions - Beauty, Kumari; Tomar, Anita; Singh, Bijay Kumar; Khan, Faraz Ahmed (Indian Forester, 2023)
The present research attempts to characterize the morphological and germination behavior of a promising fodder species Sesbania grandiflora L. (Agast) under nursery conditions. Experiment was carried out at the nursery of the Forest Research Center for Eco-Rehabilitation (FRCER), Prayagraj, Uttar Pradesh, during April 2021 and different germination parameters viz, germination per cent, survival per cent, germination capacity, germination energy, vigour index, mean daily germination and mean germination time along with seed morphological parameters were studied. Early germination from the medium-sized seeds of S. grandiflora proved to be significant under nursery conditions. A good germination per cent (83.42%) and low mean germination time (14.19 days) indicates an early and rapid germination of S. grandiflora under nursery conditions. Such an investigation may help nursery managers to produce seedlings of species for fodder availability during lean period.